Sound Kinks : Sadomasochistic Erotica in Audiovisual Music Performances - Pääkkölä, Anna-Elena (fi=Turun yliopisto|en=University of Turku|, 2016)
In this dissertation I study musical, sonic and multimodal representations of sadomasochistic erotica in films, music videos, stage performances, and popular music. The study consists of an introductory chapter (1), a theoretical chapter on sadomasochism (2), three chapters discussing six case studies (3–5), as well as discussion and conclusion chapters (6 and 7). The examples investigated are the films Secretary (2003) and Duke of Burgundy (2014), Leonard Cohen’s song ‘I’m Your Man’ (1988), Elvis Costello’s song ‘When I Was Cruel No. 2’ (2002), Rihanna’s song and music video S&M (2011), and a filmed operatic production of W. A. Mozart’s Don Giovanni focusing on the character Zerlina (1787; dir. Claus Guth, 2008). In the conclusion, I briefly discuss the film Fifty Shades of Grey (2015) as an example of post-feminist, neoliberal sadomasochism occurring at the time of writing. This study introduces a new conceptual tool for interpreting music with specific regard to eroticism: kink reading, or kink listening. My research is informed by three main areas of inquiry and methodologies: cultural musicology, queer musicology, and close reading. I theorise sadomasochism in a resolutely multifaceted and critical way using theory on performative materialism, which emphasizes both the lived experience of sadomasochism and the social power structures informing practices. My findings indicate that there are certain strategies through which SM erotica has been depicted in music, which often include a mixture of humorous musical language and semiotic signifiers of the Uncanny, or the unsettling. This combination is distinctive of depictions of SM sex scenes. The music is often encoded as multisensory, and transforms perceptions of time and place. While sadomasochist representations can reflect cultural imbalances, SM can also be utilized as a queer, critical tool for empowering non-normative bodies, genders, and sexualities by making practitioners sexual agents rather than victims. SM can also broaden the concept of sex from a genital-oriented, procreation-directed activity to a state of mind combining suspended time and space and a mixture of sexual pleasure and sexualised pain.

Sadomasokistinen erotiikka audiovisuaalisissa musiikki-esityksissä Väitöskirjassa tutkitaan sadomasokistisen erotiikan musiikillisia ja äänellisiä esityksiä nykykulttuurissa, erityisesti populaarimusiikissa ja musiikkivideossa, elokuvassa ja oopperassa. Tutkimus koostuu johdannosta (luku 1), teoreettisista tarkasteluista (luku 2), musiikillisten ja audiovisuaalisten esitysten analyyseista (luvut 3–5) sekä keskustelu- ja tulosluvuista (luvut 6–7). Tutkimusaineistona ovat elokuvat Secretary (2003) ja Duke of Burgundy (2014), Leonard Cohenin laulu ‘I’m Your Man’ (1988), Elvis Costellon laulu ‘When I Was Cruel No. 2’ (2002), Rihannan laulu ja musiikki-video S&M (2011) sekä Zerlinan henkilöhahmo W. A. Mozartin oopperan Don Giovanni (1787) nykytuotannossa (ohj. Claus Guth, 2008). Luvussa 6 käytetään myös elokuvaa Fifty Shades of Grey (2015) esimerkkinä nykypäivän sadomasokistista kuvastoa hyödyntävästä populaarikulttuurista neoliberaalina ja post-feministisenä ilmiönä. Väitöskirjassa kehitetään uusi lähestymistapa erotiikan tarkasteluun musiikissa: kink-luku eli kink-kuuntelu. Tämä perustuu kulttuuriseen musiikintutkimuksen, queer-musiikintutkimukseen sekä audiovisuaaliseen lähilukuun. SM-kuvastoa lähestytään monipuolisella tavalla performatiivisen materialismin kautta, joka painottaa sekä elettyä mielihyvää että sosiaalisia valtarakenteita, joista SM koostuu. Tutkimuksessa todetaan, että musiikissa SM-erotiikka kuvataan usein camp-huumorin kautta, johon on sekoitettu kumman (engl. Uncanny) tunnetta. Lisäksi SM:lla leikittelevät äänimaailmat laajentuvat moniaistillisiksi kokemuksiksi ja venyttävät ajan ja paikan käsitteitä. Vaikka SM voi heijastella kulttuurisia vallan epäsuhtia, sitä voidaan myös pitää queer-henkisenä kriittisenä konseptina, joka voimaannuttaa epänormatiivisia kehoja, sukupuolia ja seksuaalisuuksia tekemällä niistä aktiivisia seksuaalisia toimijoita uhriposition sijaan. Tämä voi laajentaa seksuaalisuuden ja seksuaalisen aktiviteetin käsittämistä sukupuolielinkeskeisestä ja lisääntymispäämääräisestä määrittelystä mielentilaksi, jossa aika ja paikka hämärtyvät ja jossa seksuaalinen mielihyvä ja kipu sekoittuvat nautinnollisesti.